Traumdramaturgie und Selbstreflexion: Bildstrategien romantischer Traumdarstellungen im Spannungsfeld zeitgenössischer Traumtheorie und Ästhetik - Dieckmann, Lisa (Modern Academic Publishing, 2016)
The dissertation analyses dream images in romanticist art, with regards to inherent dreamanalogue strategies in consideration of contemporary dream theory and aesthetics, with a focus on the period between 1820 and 1840. The study does not provide a typological, iconographical or motif-historical collection of samples, but analyses different aspects of selected artworks which represent a wide range in terms of their contextual, formal and topographical heterogeneity, and overcomes the existing stereotypical classification in the context of romanticist art reflection. The study identifies that, beyond the contextual-iconographical dimension, the dream serves as an aesthetical category because it is reflected not only as a motif but also in relation to its dramaturgy. In the romantic awareness of the difficulty of an adequate representation of invisible images, the nonlinear, associative, ciphered, space- and time-simultaneous structure of the dream is adapted as a method, and is staged by varied and differentiated configurations. This is mirrored by comprehensive or formal concepts (genre, technique, media and interdisciplinary), as well as in fragmentary structures (sketches and drawings), in materiality (transparency and colour) or arabesque and combinatory production principles. The study contains three chapters: after a general introduction to the subject, the analysis of the current state of research and the demonstration of the methodology in the first chapter, the second chapter focuses on contemporary dream discourses (especially the theories of Gotthilf Heinrich Schubert and Carl Gustav Carus) and the constitutive role of the philosophy of Friedrich Wilhelm Joseph Schelling. By also involving the literary concepts of dreams the romantic awareness of the deficiency of the visible image compared to the invisible, which forces an avoidance of a mimetic art perception, becomes obvious. The third chapter forms the main body of the study. On the basis of selected dream images it analyses the different artistic strategies and conditions of reception. The first section of the third chapter focuses on artist dream imagery, namely the Musician's Dream by Caspar David Friedrich, Raphael's Dream by Franz and Johannes Riepenhausen and the Dream of Erwin von Steinbach by Moritz von Schwind. The analysis indicates that the dreaming artist serves as mise-en-abyme of the dream-analogue productive and reflexive process, and the artwork itself. The second section of chapter three makes landscape spaces accessible as imaginative concepts and projections of emotional states, according to current literature studies. Landscape spaces serve as patterns for reflection processes, which is explored on the basis of The Dreamer by Caspar David Friedrich. The third section of the third chapter focuses on a combinatory and arabesque concept as a dream-analogue and self-reflexive strategy - the collage-like compilation, association and transformation of heterogeneous elements which are analysed on the basis of the artworks Dream of Adam by Moritz von Schwind and The Evening by Clemens Brentano.